Application of a control banding tool for risk level assessment and control of nanoparticles exposure in welding operations - Gomes, João (2014)
Scope of study: welding operations result in harmful emissions of nanoparticles; the aim of emissions monitorisation is to evaluate exposure levels and to derive protection measures in order to protect exposed workers; however, the traditional approach of comparing measured concentrations with exposure limits cannot be used; but risk levels can be quantified by using Control Banding Strategies.